2008
DOI: 10.1158/0008-5472.can-08-0851
|View full text |Cite
|
Sign up to set email alerts
|

Does the Renin-Angiotensin System Participate in Regulation of Human Vasculogenesis and Angiogenesis?

Abstract: Several lines of evidence suggest that hypertension and angiogenesis may be related phenomena but a functional link remains elusive. Here, we propose that the renin-angiotensin system (RAS), in addition to its central role in arterial hypertension, also regulates blood vessel formation during normal development and cancer. This mechanistic hypothesis is based on reports of biochemical, genetic, clinical, and epidemiologic data reviewed herein. Species differences between the RAS of rodents and humans likely ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…The only well-defined substrate is angiotensin III in the renin-angiotensin pathway, in which APN cleaves the NH 2 -terminal arginine residue of angiotensin III to form angiotensin IV. Consistent with several lines of evidence, we have previously identified APN as a target for inhibition of tumor vascularization and growth (18)(19)(20).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The only well-defined substrate is angiotensin III in the renin-angiotensin pathway, in which APN cleaves the NH 2 -terminal arginine residue of angiotensin III to form angiotensin IV. Consistent with several lines of evidence, we have previously identified APN as a target for inhibition of tumor vascularization and growth (18)(19)(20).…”
supporting
confidence: 86%
“…The only well-defined substrate is angiotensin III in the renin-angiotensin pathway, in which APN cleaves the NH 2 -terminal arginine residue of angiotensin III to form angiotensin IV. Consistent with several lines of evidence, we have previously identified APN as a target for inhibition of tumor vascularization and growth (18)(19)(20).Tumor growth relies on a complex microenvironment in which malignant cells cooperate with various other cell types: endothelial cells of the blood and lymphatic circulation, mesenchymal stromal cells/cancer-associated fibroblasts, and a variety of bone marrow-derived cells such as myeloid-derived suppressor cells and lymphocytes (21, 22). Some of these cell populations cooperate in inducing desmoplasia and angiogenesis.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…1 In rat studies, the pharmacological inhibition of VEGF release from podocytes has led to loss of fenestrae, endotheliosis, loss of podocytes, and proteinuria. 7,20 Khakoo et al 21 have stated that proteinuria leads to an increase in VEGF expression. Ayerder et al 22 have shown that VEGF expression is diminished significantly when blood pressure was normalized by angiotensin converting enzyme inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Vasoregulatory systems, as the KKS and the RAS, play essential roles in the maintenance of vascular homeostasis [25,26]. An understanding of the various regulatory systems controlling blood vessel growth, inflammation and pain in the joint should lead to help explain kOA progression.…”
Section: Journal Of Molecular Biomarkers and Diagnosismentioning
confidence: 99%